Degeneration of four wave mixing in 500 m step index two mode fiber - Jamaludin, J.; Zakaria, Z.; Awang, N.A.; Hadi, F.S.A.; Azmi, A.N. (UTHM Publisher, 2016)
Four wave mixing (FWM) in two-mode fiber was experimentally demonstrated at 24.7 dBm of output Erbium doped fiber amplifier (EDFA). The 0.5 km two mode fiber in laser cavity enhances the performance of four wave mixing by suppressing the homogenous broadening effect in erbium-doped fiber and perform a stable oscillation. At output EDFA approaches to 24.7 dBm, FWM is generated and the increasing of output EDFA induced the optical signal to noise ratio (OSNR) of all laser peaks.